Tube-jack testing: semi-irregular masonry wall testing - Manning, Elizabeth Campbell (2016)
Tube-jack testing is an enhanced non-destructive or minimally-destructive testing technique being developed to determine the state of stress in, and the deformability characteristics of, unreinforced masonry. This test is similar to traditional flat-jack testing, used for the same purpose. Instead of using flat-jacks, the tubejack system consists of several cylindrical jacks inserted into roughly aligned holes drilled in the mortar joints, forming an equivalent flat-jack, that can pressurize the masonry. In previous Structural Analysis of Historical Constructions Conferences, the development of this method has been presented. In this paper, testing in a masonry wall with a semi-irregular typology is presented. Two single tube-jack tests were performed to try to determine the level of stress in the masonry and one double tube-jack test was performed to estimate the deformability characteristics of the masonry. These tests are presented along with comparisons to traditional flat-jack tests performed in the same wall.